A primary Rosai-Dorfman-Destombes disease of the scalp: case report and literature review - Song, Wenxiong; Ding, Feiyu; Xiao, Yong; Hu, Xinhua; Yang, Kun; Geng, Liangyuan; Zou, Yuanjie (Frontiers in Neurology, 2023)
Abstract Background: Rosai-Dorfman disease (RDD) was first described in 1969 as a benign histiocytic proliferative disorder of unknown cause. Cases of RDD limited to cutaneous tissue have been reported over the past few decades, but single cutaneous RDD of the scalp is rare. Case presentation: We report a 31-year-old male with a lump on the parietal scalp without extranodal lesion lasting one month with gradual enlargement. The surgical incision ruptured with purulent after the first resection. Then the patient was treated with plastic surgery after disinfection and antibiotic treatment. Finally, he recovered well and discharged after 20 days. Conclusions: RDD of the scalp is rare. Surgical incision can cure the lesion but it may become infected because of increased lymphocytic infiltration. Early diagnosis and differential diagnosis of RDD are necessary. For treatment, individualized therapy is critical to patient prognosis.